Antimicrobial Potential of Strontium‐Functionalized Titanium Against Bacteria Associated With Peri‐Implantitis - Hatem Alshammari; Jessica Neilands; Christian Sloth Jeppesen; Klaus Pagh Almtoft; Ole Zoffmann Andersen; Andreas Stavropoulos (Wiley, 2024)
ABSTRACT Objectives To explore the antimicrobial potential of strontium (Sr)‐functionalized wafers against multiple bacteria associated with per‐implant infections, in both mono‐ and multispecies biofilms. Materials and Methods The bactericidal and bacteriostatic effect of silicon wafers functionalized with a strontium titanium oxygen coating (Sr‐Ti‐O) or covered only with Ti (controls) against several bacteria, either grown as a mono‐species or multispecies biofilms, was assessed using a bacterial viability assay and a plate counting method. Mono‐species biofilms were assessed after 2 and 24 h, while the antimicrobial effect on multispecies biofilms was assessed at Days 1, 3, and 6. The impact of Sr functionalization on the total percentage of Porphyromonas gingivalis in the multispecies biofilm, using qPCR, and gingipain activity was also assessed. Results Sr‐functionalized wafers, compared to controls, were associated with statistically significant less viable cells in both mono‐ and multispecies tests. The number of colony forming units (CFUs) within the biofilm was significantly less in Sr‐functionalized wafers, compared to control wafers, for Staphylococcus aureus at all time points of evaluation and for Escherichia coli at Day 1. Gingipain activity was less in Sr‐functionalized wafers, compared to control wafers, and the qPCR showed that P. gingivalis remained below detection levels at Sr‐functionalized wafers, while it consisted of 15% of the total biofilm on control wafers at Day 6. Conclusion Sr functionalization displayed promising antimicrobial potential, possessing bactericidal and bacteriostatic ability against bacteria associated with peri‐implantitis grown either as mono‐species or mixed in a multispecies consortium with several common oral microorganisms.